Level of Physical Fitness International Standard School Pilot Students at SMPN 8 Padang and SMPN 1 Rantau Pandan - Jasman, Endri; Bahdi, Masrial; Kibadra, Kibadra (Yayasan Sekora, 2018)
Based on the symptoms of the level of physical fitness of the International Standard School Pilot Project (RSBI), SMPN 8 Padang is better than SMPN 1 Rantau Pandan, Bungo Regency, so the problem is the difference in the level of physical fitness. This study aims to determine the differences in the level of physical fitness of RSBI students at SMPN 8 Padang and SMPN 1 Rantau Pandan, Bungo Regency. This study is an espost facto, to determine differences in the level of physical fitness, the population of this study were 304 students of class VIII RSBI SMPN 8 Padang and SMPN 1 Rantau Pandan, Bungo Regency, with the sampling technique used was purposive sampling, namely the sampling represented by each VIII grade male student school. A as many as 52 people. The tool used for data collection was a physical fitness test, then analyzed by descriptive method. To determine the difference test is done by using the